Insights from a multibeam echosounder to survey pelagic fish shoals and their spatio-temporal distribution in ultra-shallow waters. (5th January 2022) - David, Viviane; Mouget, Anne; Perrot, Yannick; Le Goff, Loïc; Thiriet, Pierre; Diogoul, Ndague; Feunteun, Eric; Acou, Anthony; Brehmer, Patrice
Abstract: Surveying pelagic fish population dynamics in ultra-shallow waters (<20m) is often limited by research vessel size, which not usually navigate in shallow waters. Here, we use a multibeam echosounder to detect fish shoals and assess their characteristics (acoustic density and 3-D morphology) in ultra-shallow waters to follow European Marine Strategy Framework Directive (MSFD) request. Surveys were made in two coastal areas in French Brittany during different seasons (spring, summer, autumn) in 2020. Our surveying methodology applying portable multibeam echosounder on small vessels allowed us to successfully survey pelagic fish spatio-temporal distributions in ultra-shallow waters. Numerous shoals have been observed which could account for important biomass and they were significantly denser and larger in ultra-shallow waters compared to shoals in deeper areas for both study sites. Shoal surfaces and volumes were also significantly lower in autumn compared to spring and summer. In addition, Atlantic mackerels ( Scomber scombrus ) were observed in ultra-shallow waters areas during summer in both study sites. Consequently, the multibeam echosounder is a workable and relevant tool for setting up long-term surveying of pelagic fish in ultra-shallow waters (coastal and estuarine ecosystems) as required by the MSFD to better assess pelagic fish ecological status. Highlights: Insights of a multibeam echosounder to survey pelagic fish in ultra-shallow waters (<30 m). Surveys made in two coastal areas in French Brittany during different seasons in 2020. Important biomass of pelagic fish in ultra-shallow waters. Shoal surfaces and volumes was lower in autumn compared to spring and summer.